Harmful Algal Blooms (HABs) and Public Health: Progress and Current Challenges (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
Over the past decade, coastal and freshwater systems in the U.S. and worldwide have experienced an apparent increase in the frequency and geographic distribution of harmful algal blooms (HABs). These blooms can adversely affect both public health and ecosystem health. Toxin-producing HABs can accumulate in drinking and recreational waters and in foods of aquatic origin such as fish and seafood. Human and animal health risks include exposure to the toxins through eating contaminated food or drinking or swimming in contaminated water. Because of these potential public health risks, several countries and U.S. states have developed monitoring programs and guidelines for drinking and recreational water quality to protect public health. This special issue will present research papers and reviews on various aspects of public health and environmental responses to harmful algal blooms. [...]